2020
DOI: 10.33417/tsh.739505
|View full text |Cite
|
Sign up to set email alerts
|

Üni̇versi̇te Öğrenci̇leri̇ni̇n Ai̇le Ai̇di̇yeti̇ni̇n Ai̇le İli̇şki̇leri̇ Açisindan İncelenmesi̇

Abstract: açısından incelenmesine ve diğer örneklem gruplarında da çalışma yapılmasının aile çalışmalarına katkı sunacağı düşünülmektedir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…In a study conducted, results supporting the findings were obtained. Considering the perceived family attitude, it was concluded that the family belonging of university students who thought that their family was democratic was higher than other perceived family attitudes (Aslantürk et al, 2020). A different study concluded that the family belonging of students who perceived their family attitude as indifferent was lower than those who perceived it as democratic, authoritarian, and overly caring/protective (İlik, 2019).…”
Section: Analyses and Resultsmentioning
confidence: 99%
“…In a study conducted, results supporting the findings were obtained. Considering the perceived family attitude, it was concluded that the family belonging of university students who thought that their family was democratic was higher than other perceived family attitudes (Aslantürk et al, 2020). A different study concluded that the family belonging of students who perceived their family attitude as indifferent was lower than those who perceived it as democratic, authoritarian, and overly caring/protective (İlik, 2019).…”
Section: Analyses and Resultsmentioning
confidence: 99%
“…Ancak çeşitli kurumlar ve kişiler arasında aile; bireylerin bireyler arası ilişkileri ilk tecrübe edindiği ve bu tecrübelerden öğrenebildiklerini başka ilişkilerine aktarabildiği toplumsal bir yapı olmasından kaynaklı olarak diğerlerinden farklılık göstermektedir. Çocukluk dönemlerinde aile büyükleriyle olan ilişkiler, aileye karşı duyulan aidiyet, bireyin gelecekte yakından inşa edeceği ilişkileri ve işlevselliklerini direkt veya dolaylı yönden etkileyebilmektedir (Aslantürk, Kesen ve Daşbaş, 2020). İşletmelere veya diğer bireylere karşı aidiyet geliştirme olasılığı aile aidiyeti fazla olan bireylerde daha yüksektir.…”
unclassified